2017
DOI: 10.18203/2349-3291.ijcp20172658
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of childhood epilepsy in Nigerian children seen in a tertiary hospital

Abstract: Background: Epilepsies are the most common conditions encountered in most paediatric neurology clinics in many parts of the developing world. In sub-Saharan Africa epilepsies are secondary, reflecting persistently high risks at birth, and the adverse neurological sequelae of CNS infections during and beyond childhood. The study was designed to determine the clinical pattern of childhood epilepsies, probable aetiologies and associated comorbidities of the disease children.Methods: The study was conducted within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 6 publications
4
15
2
1
Order By: Relevance
“…Similar findings have been reported from other parts of Africa [10,11] and Europe [12,13]. However, Eyong et al [14] in their study in South Nigeria reported generalized epilepsy as the commonest epilepsy type seen. The perceived difference is most likely due to the incorporation of EEG findings in diagnosis in our study since the study by Eyong et al [14] was based solely on history obtained from parents/caregivers (eye witness account).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar findings have been reported from other parts of Africa [10,11] and Europe [12,13]. However, Eyong et al [14] in their study in South Nigeria reported generalized epilepsy as the commonest epilepsy type seen. The perceived difference is most likely due to the incorporation of EEG findings in diagnosis in our study since the study by Eyong et al [14] was based solely on history obtained from parents/caregivers (eye witness account).…”
Section: Discussionsupporting
confidence: 85%
“…However, Eyong et al [14] in their study in South Nigeria reported generalized epilepsy as the commonest epilepsy type seen. The perceived difference is most likely due to the incorporation of EEG findings in diagnosis in our study since the study by Eyong et al [14] was based solely on history obtained from parents/caregivers (eye witness account). Additionally, it may be because some of the focal seizures or focal to bilateral tonic-clonic seizures were wrongly classified as generalized seizures.…”
Section: Discussionmentioning
confidence: 90%
“…Eyong et al .,12 in a tertiary health facility in southern Nigeria, saw 107 children with epilepsy in a 1-year period. The large proportion of patients in this study who had no form of treatment for long periods is not surprising and reflects the general belief in Africa that epilepsies are not treatable with orthodox medication 4567121314. This also most probably informed the choice of traditional herbalists by some of our patients prior to presentation to us.…”
Section: Discussionmentioning
confidence: 99%
“…While Rolandic epilepsy is well recognized and appears in studies on epilepsies in Nigeria, PS is underdiagnosed and escaping recognition. [6][7][8][9] The three cases reported all had at the onset unusual autonomic (focal, nonmotor) symptoms such as vomiting, ictal syncope ("lifeless and floppy body"), behavior change and cyanosis/ palor ("colour change", "dark lips and palms"). These initial symptoms are difficult for the General practitioner or even Paediatricians to recognize as ictal events and failure to do so is a major reason for misdiagnosis of PS.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, this common childhood epileptic syndrome remains under diagnosed in Nigeria as there are no reports or mention of it in studies on epilepsy in Nigeria. [5][6][7][8] The three cases reported here all manifested the unusual constellation of autonomic symptoms in addition to the conventional seizure symptoms. One of the cases had visual hallucinations which are rare in PS while another had adverse natal, perinatal and early postnatal events that suggested a symptomatic aetiology for the autonomic seizures.…”
Section: Introductionmentioning
confidence: 99%